Analysis of the Role of Islamic Microfinance Institutions in the Development of MSMEs in Indonesia - Niken Baramurti Evieta Enggar Sandy (Universitas Darussalam Gontor, 2023)
Micro, Small and Medium Enterprises (MSMEs) in Indonesia are one of the instruments that can increase economic growth. With the importance of the function of MSMEs, MSMEs in Indonesia should receive support so that they can grow and develop. This paper examines the influence of Islamic Microfinance in creating innovative sustainable financing models for MSMEs in Indonesia. The discussion in this paper offers innovations in sustainable financing and capital models carried out by Islamic Microfinance Institutions (LKMS) for increasing MSMEs in Indonesia. This research uses the descriptive qualitative method. The results of this study indicate that sustainable financing initiated by LKMS has a significant role in increasing MSMEs in Indonesia. Where this will also help increase state income through MSMEs and help alleviate poverty in Indonesia